Perizinan Tenaga Kerja Asing dalam Perspektif Hukum Administrasi Negara dan Perlindungan Tenaga Kerja Nasional di Indonesia - Aditia Thaariq Syah; Endeh Suhartini; Togar Natigor Siregar (PMIH Untag Semarang, 2026)
This study analyzes the legal regulation and licensing mechanism for the employment of foreign workers in Indonesia and examines its implications for the protection of national labor. The research uses a normative juridical approach through the analysis of statutory regulations, legal literature, and relevant scholarly works. The findings indicate that the post–Job Creation Law regulatory framework has simplified administrative procedures through the Foreign Worker Utilization Plan (RPTKA) and digital licensing systems. However, practical implementation still reveals administrative violations, weak inter-agency supervision, and limited effectiveness of technology transfer obligations. These conditions create potential risks to job opportunities, bargaining power, and welfare of domestic workers. From the perspectives of labor law and administrative law, effective protection requires strengthened supervision, integrated data systems, consistent law enforcement, and sustainable human resource development policies. The study concludes that the balance between investment facilitation and labor protection can only be achieved through a justice-oriented regulatory reconstruction that prioritizes national workforce competitiveness while maintaining legal certainty and social welfare.